INDUSTRY 4.0: CONCEPTS, CHALLENGES AND EXPECTATIONS: INDÚSTRIA 4.0: CONCEITOS, DESAFIOS E EXPECTATIVAS - Neiva, Laédna Souto; de Menezes, Laura Nunes; de Alencar Lira, Marcela Cristine; Brasileiro, Maria Isabel (Brazilian Journal of Production Engineering, 2020)
Smart manufacturing, through the Industry 4.0 concept, is becoming the reality of many industry segments today, and the tendency for the future is to strengthen this concept by becoming the usual everyday modus operandi of industrial environments. It is therefore up to industry professionals and organizations to invest in advanced training and qualification aligned with the requirements and challenges of Industry 4.0. Aligned this context, the aim of this review paper is to present the academic as well as the industrial communities an informations compiled based on literature about the elementary concepts, requirements, and challenges that this new and emerging industrial stage presents and imposes on the modern world from now on. From the information presented in this article it can be concluded that smart manufacturing, the basis of operation of Industry 4.0, presents among other benefits the ability to face undesirable events since the systems can count alternative operation plans for emergency, unforeseen and In addition, smart manufacturing proposes smart sorting systems that aim to minimize manufacturing costs such as input wastage. Finally, Industry 4.0 should be understood as an industrial process management system that integrates a multitude of concepts, ideas and technologies in order to optimize the efficiency of industrial productions.